Uncertainty and Change: Survey Evidence of Firms's Subjective Beliefs - Ruediger Bachmann; Kai Carstensen; Stefan Lautenbacher; Martin Schneider (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper studies how managers plan under uncertainty. In a new survey panel on German manufacturing firms, we show that uncertainty reflects change: Planning incorporates higher subjective uncertainty about future sales growth when the firm has just experienced unusual growth, and more so if the experience was negative. At the quarterly frequency, subjective uncertainty closely tracks conditional volatility of shocks: Both exhibit an asymmetric V-shaped relationship with past growth. In the cross section of firms, however, subjective uncertainty differs from conditional volatility: planning in successful firms—either large or fast-growing—reflects lower subjective uncertainty than in unsuccessful firms even when the size of the shocks is the same.
Keywords: C83; D22; E20; E23; 330; expectation formation; firms; measurement; subjective uncertainty; survey data